2005
DOI: 10.1021/bi0477992
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxynaphthaldehyde Phosphate Derivatives as Potent Covalent Schiff Base Inhibitors of Fructose-1,6-bisphosphate Aldolase

Abstract: Interactions of phosphate derivatives of 2,6-dihydroxynaphthalene (NA-P(2)) and 1,6-dihydroxy-2-naphthaldehyde (HNA-P, phosphate at position 6) with fructose-1,6-bisphosphate aldolase from rabbit muscle were analyzed by enzyme kinetics, difference spectroscopy, site-directed mutagenesis, mass spectrometry, and molecular dynamics. Enzyme activity was competitively inhibited by NA-P(2), whereas HNA-P exhibited slow-binding inhibition with an overall inhibition constant of approximately 24 nM. HNA-P inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Similarly to salicylic derivative 44 , the presence of the hydroxyl group ortho to the aldehyde in 46 proved to be essential in determining its mechanism of action (Schiff base formation). [161] Hexitol diphosphate, consisting in a diastereoisomeric mixture of glucitol bisphosphate ( 47 ) and mannitol bisphosphate ( 48 ), had been known a long time as a competitive inhibitor of class I muscle ALD ( K i ~1.2 μM). [162] More recently 47 and 48 were separately tested on rabbit muscle aldolase, and they both behaved as competitive inhibitors with K i values of 100 μM ( 47 ) and 7.3 μM ( 48 ).…”
Section: Glycolytic Effectors As Potential Targets In Cancer Therapymentioning
confidence: 99%
“…Similarly to salicylic derivative 44 , the presence of the hydroxyl group ortho to the aldehyde in 46 proved to be essential in determining its mechanism of action (Schiff base formation). [161] Hexitol diphosphate, consisting in a diastereoisomeric mixture of glucitol bisphosphate ( 47 ) and mannitol bisphosphate ( 48 ), had been known a long time as a competitive inhibitor of class I muscle ALD ( K i ~1.2 μM). [162] More recently 47 and 48 were separately tested on rabbit muscle aldolase, and they both behaved as competitive inhibitors with K i values of 100 μM ( 47 ) and 7.3 μM ( 48 ).…”
Section: Glycolytic Effectors As Potential Targets In Cancer Therapymentioning
confidence: 99%
“…This species, whose presence was confirmed by spiking the STS-catalyzed reaction with an authentic sample of independently synthesized 4-diFME1 [3] (Figure 3 F), is formed as an unstable intermediate and rapidly decomposes to give 4-FE1 ( Figure 3 F and G). Because aldehydes have been known to act as highly potent and sometimes almost irreversible enzyme inhibitors, [10] we reasoned that inactivation of STS by compound 4 might be mainly due to inhibition by 4-FE1. Indeed, incubation of STS with just 4-FE1 resulted in time and concentration-dependent inhibition of STS (Figure 4 A).…”
mentioning
confidence: 99%
“…[13] Although the site of STS modification by 4-FE1 has yet to be established, it is highly likely that it is forming a Schiff base with an active-site residue because it has been shown that certain aldehydes can function as almost irreversible enzyme inhibitors through the formation of stable Schiff base adducts with residues bearing side-chain amines. [10] Lys368 in the active site of STS is a strong candidate for Schiff base formation A C H T U N G T R E N N U N G because it is in close proximity to the 4-position of estrone, which has been modeled into the active site of STS. [14] It is possible that the formyl group of 2-FE1 cannot attain the correct geometry or is too far removed from Lys368 to form a stable Schiff base.…”
mentioning
confidence: 99%
“…Schistosome cells express FBPA that upon degradation give rise to similar antigenic peptides that are presented on the cell surface complexed with MHC class I molecules (MHC I), that greatly affects the antigenic peptide repertoire presented to cytotoxic T lymphocytes (Apcher et al 2010;Zervoudi et al 2013), and as a result cannot develops cytotoxic cellular responses contributing to immune evasion by schistosome cells. Unlike the other molecules of S. japonicum, such as protein arginine methyltransferase 1 and allergen-like protein 1, which could induce mouse bone marrow-derived dendritic cell (BMDC) to mature and therefore activate their immune response (Diao et al 2014), or induce a polarized Th2 immune response by increasing specific antibody significantly in S. japonicum-infected mice (Chen et al 2010), sjFBPA contains similar antigenic peptides with that of human FBPAs and may contribute to immune evasion of S. japonicum from their host, human being. This result would be confirmed by some animal experiment.…”
Section: Discussionmentioning
confidence: 99%